Geometric modeling and analysis of a novel modified wrap for scroll compressors. (May 2019) - Wang, Jun; Cao, Chenyan; Cui, Shujie; Wang, Zengli
Abstract: A geometric model of a 1-pair of circular arcs modified wrap (1-CMW), the existing circular arc modified wrap (CMW), was developed. In order to improve the performance and overcome its shortcoming of the CMW, a novel n -pair of circular arcs modified wrap ( n -CMW) for scroll compressors was proposed based on the midline design method. A 2-CMW was analyzed, and then a general geometric model of n -CMW with arbitrary pair number n was established. In addition, the generation procedure, general mutual dependence of geometric parameters as well as equations of wrap profiles were obtained, and the influence of geometric parameters on shapes of the n -CMW was analyzed. Flow simulations of the 1-CMW, 2-CMW, 3-CMW and 4-CMW during the working process with the same conditions were conducted. Study results indicate that the proposed n -CMW increases the built-in volume ratio and design flexibility, and is superior to the existing CMW.